2009
DOI: 10.1002/ejsp.643
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive normative beliefs and conservation behavior: The moderating roles of personal involvement and injunctive normative beliefs

Abstract: There is ample evidence of the power of social influence on pro-environmental behaviors. Beliefs about the conservation behavior of others (descriptive normative beliefs) have a strong positive correlation with one's own conservation actions. However, this relationship has not been investigated much further in terms of possible moderators or involved mechanisms of information processing. The present study examines two potential moderators and draws links to underlying processing mechanisms. We hypothesized tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
219
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(253 citation statements)
references
References 40 publications
26
219
0
8
Order By: Relevance
“…Social norms are rules or standards for behavior among members of a group (Sherif, 1965;Turner, 1991) and they can be categorized in two main ways: as injunctive norms (i.e., perceptions of what people ought to do) and descriptive norms (i.e., what people actually do). We focus on descriptive norms in particular in this study, as they have been shown in previous research to predict a variety of pro-environmental behaviors, such as reduced littering (Cialdini, Reno, & Kallgren, 1990), increased recycling (Fornara, Carrus, Passafaro, & Bonnes, 2011;Nigbur, Lyons, & Uzzell, 2010;Schultz, 1999), use of public transport or bicycles rather than personal cars (Kormos, Gifford, & Brown, 2015), and energy conservation (Göckeritz et al, 2010;Nolan, Schultz, Cialdini, Goldstein, & Griskevicius, 2008).…”
Section: The Role Of Perceived Social Normsmentioning
confidence: 99%
“…Social norms are rules or standards for behavior among members of a group (Sherif, 1965;Turner, 1991) and they can be categorized in two main ways: as injunctive norms (i.e., perceptions of what people ought to do) and descriptive norms (i.e., what people actually do). We focus on descriptive norms in particular in this study, as they have been shown in previous research to predict a variety of pro-environmental behaviors, such as reduced littering (Cialdini, Reno, & Kallgren, 1990), increased recycling (Fornara, Carrus, Passafaro, & Bonnes, 2011;Nigbur, Lyons, & Uzzell, 2010;Schultz, 1999), use of public transport or bicycles rather than personal cars (Kormos, Gifford, & Brown, 2015), and energy conservation (Göckeritz et al, 2010;Nolan, Schultz, Cialdini, Goldstein, & Griskevicius, 2008).…”
Section: The Role Of Perceived Social Normsmentioning
confidence: 99%
“…When studying proenvironmental or green behaviors, the independent influence of injunctive and descriptive norms has been continuously supported including the examination of littering [19], energy conservation [22,23], purchase of organic and fair-trade apparel [24], participation in a hotel's environmental conservation program [25], and recycling behaviors [26].…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…The ABM model developed by Azar and Menassa [12,87] is based on an RA concept. Additionally, Verplanken and Wood [104] and Göckeritz et al [105] employed RA concepts to simulate pre-environmental behaviors of occupants in order to understand occupants' responses to the new energy characteristics of their built environment. Their results shows that an occupant's energy-conserving behavior is highly connected to his/her belief regarding other occupants' energy-conserving behaviors.…”
Section: Other Techniquesmentioning
confidence: 99%
“…Verplanken and Wood [104] and Göckeritz et al [105] discussed how improving occupants' energy behaviors first requires changing individuals' beliefs and intentions regarding energy use. In this context, periodically holding energy meetings and workshops for occupants in individual commercial buildings has shown to be effective in improving energy-saving knowledge of built environments.…”
Section: Improving Occupant Energy-consuming Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation